Android Apps for Laundry using Model View Presenter Pattern - Dihin Muriyatmoko; Taufiqurrahman Taufiqurrahman; Mukhlas Munif Ahsani (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2023)
Universitas Darussalam (UNIDA) Gontor is a boarding-based campus that requires its professors and students to live 24 hours a day in the dormitory. To support UNIDA Gontor's household needs, one includes washing clothes; the campus has created the Unit Usaha UNIDA (U3) laundry service. This laundry service provides cleaning services based on weight and processing time, divided into three packages: regular, express, and special. Currently, the laundry service runs its administrative process using books, paper notes, and social media, Whatsapp, for communication with customers. As the laundry service grows, customers need help determining their clothing status. The same is true for employees who need help dealing with the increasing number of orders and answering the status of customer clothing one by one. This research aims to speed up the administrative process of the U3 laundry service, especially in terms of order status. The method used to help solve the problem is an Android-based mobile app that implements the Model View Presenter pattern. The black-box method and a questionnaire to customers and laundry employees were used to test this research. The results of the black-box test showed that all the features provided are running smoothly without errors. Meanwhile, the results of a random questionnaire to ten customers and four employees regarding ease, design, information, and benefits showed high satisfaction. The results of all tests prove that this application is easy for customers, especially in determining the status and cost of laundry. In addition, employees also find it easy to update and store order data, making it faster, neater, and safer. The suggestion for future research is to add a cost feature for clothing that uses hangers and plastic and to add real-time notification features using firebase.